Late Guadalupian–early Lopingian marine geochemical records from the Upper Yangtze, South China: Implications for climate-biocrisis events - Li, Ruixuan; Sun, Shi; Xia, Wenpeng; Chen, Anqing; Ogg, James G.; Yang, Shuai; Xu, Shenglin; Liao, Zhiwei; Yang, Di; Hou, Mingcai (Frontiers in Earth Science, 2023)
Major paleoenvironmental changes occurred during the Guadalupian-Lopingian boundary (GLB) transition, but the causative linkages among the Emeishan Large Igneous Province (LIP), end-Guadalupian crisis and climatic fluctuations are still in dispute. Variation of geochemical proxies preserved in the sedimentary records is important evidence in examining potential links between volcanisms and environmental changes. Herein, we carried out a comprehensive study of carbon/strontium isotope and trace element geochemistry at the Dukou section, northern margin of the Upper Yangtze. During the Late Guadalupian, the carbon isotope showed a negative drift, the marine primary productivity declined simultaneously, and redox proxies indicate the enhancement of ocean oxidation. It is worth noting that the δ13Ccarb turns into a rapid negative drift from a slow decline at approximately 260.55 Ma, which was almost synchronized with the latest reported eruption ages of Emeishan LIP. This coincidence suggests that global volcanic-tectonic activity during the Late Guadalupian might have been the dominant important factor in carbon-cycle perturbation. Subsequently, the δ13Ccarb presents a rapid positive shift at approximately 259.4 Ma, and climate transformed from interglacial to P4 glacial, indicating that the climate rapidly cooled before the Emeishan LIP completely ended, which may be due to carbon sinks caused by weathering of mafic rocks, and may also be associated with a significant reduction in global volcanic activity. Accompanied by sudden weathering attenuation, the 87Sr/86Sr ratios show a significant increase instead from the previous long-time low value, which only can be explained reasonably by the rapid decline in mantle-derived Sr flux associated with the weakening of volcanic activity and mafic weathering. Intergrated geochemical indices in this interval shows that there is a rapid climate perturbation associated with a significant δ13Ccarb negative shift at approximately 260.55 Ma ∼ 259.10 Ma, which may be related to the eruption surge of the Emeishan LIP and, active volcanic arcs, whichand triggered a transient warming event and the end-Guadalupian biocrisis.